1994
DOI: 10.1128/iai.62.4.1213-1218.1994
|View full text |Cite
|
Sign up to set email alerts
|

Size heterogeneity among antigenically related Giardia lamblia variant-specific surface proteins is due to differences in tandem repeat copy number

Abstract: Giardia lamblia undergoes antigenic variation by modulating the expression of the different genes that comprise the trophozoite's variant-specific surface protein (VSP) repertoire. We studied an epitope that is conserved among VSPs expressed by cloned trophozoite lines derived from the independent G. lamblia isolates WB, G3M, Be-2, and CAT. The epitope recognized by monoclonal antibody 6E7 lies entirely within the region of tandemly repeated 65-amino-acid units that is characteristic of these size-variant VSPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 26 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…(iii) At least four ariel genes are constitutively expressed, so antigenic diversity may exist within a single parasite isolate rather than between separate parasite isolates (as is the case for SREHP and amebic chitinase) (4,22). It is unclear whether amebae have any variably expressed antigens, such as the var proteins of P. falciparum, the variable surface proteins of Giardia lamblia, and the variable surface glycoproteins of Trypanosoma brucei (3,18,27).…”
Section: Ariel Octapeptide Repeats (D/n/s-e-s-s-d/n-n-k-p) Are Identimentioning
confidence: 99%
“…(iii) At least four ariel genes are constitutively expressed, so antigenic diversity may exist within a single parasite isolate rather than between separate parasite isolates (as is the case for SREHP and amebic chitinase) (4,22). It is unclear whether amebae have any variably expressed antigens, such as the var proteins of P. falciparum, the variable surface proteins of Giardia lamblia, and the variable surface glycoproteins of Trypanosoma brucei (3,18,27).…”
Section: Ariel Octapeptide Repeats (D/n/s-e-s-s-d/n-n-k-p) Are Identimentioning
confidence: 99%
“…VSPs are proteins with frequent CXXC motifs and are transported through the ER by their signal peptides (McCaffery and Gillin, 1994). To date, all known VSPs are membrane proteins that contain similar 25‐amino acid transmembrane domain and a highly conserved CRGKA cytoplasmic tail (Mowatt et al ., 1994). This conserved C‐terminus may function as a membrane‐anchoring domain (Papanastasiou et al ., 1996) or as a sorting motif to the plasma membrane (Marti et al ., 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Antigenic variation in Giardia involves variantspecific surface proteins (VSPs) (86). VSPs are key players in Giardia antigenic variation and are the focus of great controversy in the field because their characteristics may be related to regulation of the switching process (29).…”
Section: Variant-specific Surface Proteinsmentioning
confidence: 99%
“…It was later demonstrated that all vsp genes are transcribed but that all but one are silenced by an RNA interference (RNAi)-like mechanism. This mRNA always corresponds to the variant expressed on the parasite surface (5,85,86). After VSP switching occurs, the original transcript disappears with the appearance of a distinct VSP mRNA (3, 85,144,147).…”
Section: Molecular Mechanisms Involved In Antigenic Variationmentioning
confidence: 99%